2020
DOI: 10.1186/s13017-019-0285-7
|View full text |Cite
|
Sign up to set email alerts
|

Timing of early laparoscopic cholecystectomy for acute calculous cholecystitis revised: Protocol of a systematic review and meta-analysis of results

Abstract: Background: Early laparoscopic cholecystectomy has been adopted as the treatment of choice for acute cholecystitis due to a shorter hospital length of stay and no increased morbidity when compared to delayed cholecystectomy. However, randomised studies and meta-analysis report a wide array of timings of early cholecystectomy, most of them set at 72 h following admission. Setting early cholecystectomy at 72 h or even later may influence analysis due to a shift towards a more balanced comparison. At this time, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 27 publications
1
35
1
3
Order By: Relevance
“…Uncomplicated cholecystitis with an indication for surgery warrants no antibiotics beyond the operating room, unless there are criteria such as perforation, gangrene or empyema defining complicated cholecystitis; uncomplicated diverticulitis is usually managed medically, and surgical diverticulitis (e.g., perforated diverticulitis) is proposed to be treated postoperatively for 4 days, providing that source control has been adequate [ 27 ]. In our study, there was a trend towards a shortened duration of postoperative EAT, but the difference was not significant expect for the treatment duration in cholecystitis, in compliance with current guidelines [ 28 , 29 ]. To address this matter of the extended continuation of postoperative antibiotics, our AMS team developed hospital-specific guidelines on medical and surgical IAIs, a multidisciplinary effort with the joint participation of the departments of general surgery, hepatology and gastroenterology.…”
Section: Discussioncontrasting
confidence: 54%
“…Uncomplicated cholecystitis with an indication for surgery warrants no antibiotics beyond the operating room, unless there are criteria such as perforation, gangrene or empyema defining complicated cholecystitis; uncomplicated diverticulitis is usually managed medically, and surgical diverticulitis (e.g., perforated diverticulitis) is proposed to be treated postoperatively for 4 days, providing that source control has been adequate [ 27 ]. In our study, there was a trend towards a shortened duration of postoperative EAT, but the difference was not significant expect for the treatment duration in cholecystitis, in compliance with current guidelines [ 28 , 29 ]. To address this matter of the extended continuation of postoperative antibiotics, our AMS team developed hospital-specific guidelines on medical and surgical IAIs, a multidisciplinary effort with the joint participation of the departments of general surgery, hepatology and gastroenterology.…”
Section: Discussioncontrasting
confidence: 54%
“…Several of these conditions demand surgical intervention, and hospitals have to cope with and address emergency surgeries. Care should be taken to avoid transmission for patients and medical staff during these surgeries [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In COVID-19 patients, the metabolic alterations were also detectable in the recycle system. 90 , 91 By performing proteomic and metabolomic profiling of sera from COVID-19 (n = 46) and control individuals (n = 53), Shen et al revealed characteristic protein and metabolite changes in the sera of severe COVID-19 patients, which might be used in selection of potential blood biomarkers for severity evaluation. 92 The serum metabolites of COVID-19 patients were also evaluated to investigate metabolic effects of SARS-CoV-2 infection which identified that amino acid (tryptophan, gluconeogenic and sulfur-containing amino acid) and fatty acid (acylcarnitines and free fatty acids) metabolism are correlated with COVID-19 disease.…”
Section: Pathogenesis Of Coronaviruses In Humanmentioning
confidence: 99%